Defense technology development: does every country need an organization like DARPA?. Issue 1 (2nd January 2016) - Durmaz, Mahmut
Abstract : The Defense Advanced Research Projects Agency (DARPA) of the United States tries to create transformational defense technology that not only benefits the US military, but also its economy. With its ability to integrate civilian industry in the R&D process, DARPA taps into the knowhow and knowledge of the whole country. The dual-use systems DARPA develops enable the defense industry as well as other industries to reap the benefits of technological developments. DARPA's program managers, who are experts in their field are the driving force for the innovations because they generate and put forward new ideas that can have a revolutionary impact on technology. They venture into various industries, universities, labs, and companies to seek new and far-fetched ideas that can turn into reality. This strong and independent manager program enables risk-taking and encourages creativity and innovation. DARPA's achievements and techniques could be an inspiration and guidance to other countries with the need for strong defense forces. The purpose of this study is to understand what makes DARPA successful and find out whether every country needs an organization like DARPA. Although it requires a considerable budget, countries can benefit from establishing and maintaining an organization like DARPA as it will help these countries in the long run by making them ready to fight the next war and by creating advanced technology that can serve the whole nation and the world.